INTEGRATION OF DIGITAL CUSTOMER EXPERIENCE, SOCIAL CAPITAL, AND EMOTIONAL BRANDING IN STRENGTHENING TRADITIONAL CULINARY MSMES IN EAST KALIMANTAN - Zilfana Zilfana; Rina Masithoh Hariyadi; Heriyanto Heriyanto; Camelia Verahastuti (Sekolah Tinggi Ilmu Ekonomi Widya Wiwaha, 2025)
This qualitative research with a multi-case approach explores how digital consumer experiences, social support, and emotional branding interact to strengthen the presence of micro, small, and medium enterprises in the traditional food sector in East Kalimantan. Data collection was conducted through in-depth interviews, observations, and documentation involving business owners, community influencers, and government representatives in Samarinda, Balikpapan, and Bontang. The results show that consumer experiences in the digital world are influenced not only by the ease of platform navigation but also by community-based interactions such as online recommendations, shared content, and digital participation campaigns. Social support is built through trust in the community, local networks, and micro-influencers who play an important role in transferring reputation to MSME brands. Emotional branding arises from cultural stories, traditional family recipes, feelings of nostalgia, and the application of local identity in digital messages. The combination of these three aspects creates a hybrid cultural-digital model, where offline community engagement strengthens the online experience, and digital narratives reinforce emotional engagement and brand loyalty. This study contributes to theory by expanding the model of cooperation between culture and digital. It shows that the combination of DCE, social capital, and emotional branding is very important for increasing customer loyalty and long-term business sustainability among traditional food MSMEs in East Kalimantan. In practice, this study provides a strategic perspective for creating digital branding initiatives that focus on community and cultural stories.